2000
DOI: 10.1093/carcin/21.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of benzo[a]pyrene diolepoxide-DNA adduct levels in human white blood cells by CYP1A1, GSTM1 and GSTT1 polymorphism

Abstract: The modulation of benzo[a]pyrene diolepoxide (BPDE)-DNA adduct levels by polymorphisms in the CYP1A1, GSTM1 and GSTT1 genes was assessed in leukocytes of Caucasian males. Eighty-nine coke oven workers (35 smokers, 36 ex-smokers and 18 non-smokers) were recruited from job categories with different exposure levels to polycyclic aromatic hydrocarbons (PAH), together with 44 power plant workers (all smokers) not exposed to PAH. BPDE-DNA adducts were detected in 69 of 133 (52%) DNA samples with a 100-fold variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(71 citation statements)
references
References 30 publications
4
65
0
1
Order By: Relevance
“…The effects of metabolic enzyme polymorphisms on PAH-DNA adduct levels are usually detected at high PAH exposures only, e.g., occupational exposure in coke-oven plants. 32,33 However, no effect was found among those with low-level exposure. 30 This might partly explain why no associations were found between PAH-DNA adduct levels and polymorphisms of GSTM1 and GSTP1 in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The effects of metabolic enzyme polymorphisms on PAH-DNA adduct levels are usually detected at high PAH exposures only, e.g., occupational exposure in coke-oven plants. 32,33 However, no effect was found among those with low-level exposure. 30 This might partly explain why no associations were found between PAH-DNA adduct levels and polymorphisms of GSTM1 and GSTP1 in our study.…”
Section: Discussionmentioning
confidence: 93%
“…31 However, the GSTM1 genotype did have an effect on adduct formation among coke-oven workers. 32,33 Combined GSTM1 and GSTP1 genetic polymorphisms also affected adduct levels in cigarette smokers. 34 However, when GSTP1 genotypes alone were compared, no statistically significant differences in adduct levels were found 34 nor were there associations between maternal white blood cell PAH-DNA adduct levels and maternal GSTP1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA expression studies showed relative expression of CYP2D6 in myeloblastic and lymphoid cell lines [5]. CYP1A1*2A variant has an increased activity, associated with a higher level of DNA adduct formation, and increased risk of carcinogenesis [48][49][50][51]. CYP1 family enzyme expressions are increased in myeloblastic and lymphoid cell lines, and CYP1 enzymes may contribute to the carcinogenesis of hematopoietic cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a positive correlation has been reported between the incidence of lung cancer and the inducibility of AHH in human lymphocytes (Gahmberg 1979;Kellerman et al 1973;Kiyohara et al 1998). Certain alleles of the human CYP1A1 gene have been implicated both in lung cancer and in prostate cancer in Japan (Hayashi et al 1992;Murata et al 1998;Rojas et al 2000), but these observations have not been reproduced in studies on Caucasian populations where the indicated alleles appear at much lower frequencies. Two closely linked mutations in particular have been studied extensively in relation to cancer risks; one results in a new restriction site (MspI) in the 3ú ntranslated region of the gene, and the other is a mutation in the 7th exon that results in an amino acid exchange (Ile to Val).…”
Section: Pah Exposure In Humansmentioning
confidence: 99%